Objective Physiological Measurements but Not Subjective Reports Moderate the Effect of Hunger on Choice Behavior - Shabat-Simon, Maytal; Shuster, Anastasia; Sela, Tal; Levy, Dino J. (Frontiers in Psychology, 2018)
Hunger is a powerful driver of human behavior, and is therefore of great interest to the study of psychology, economics and consumer behavior. Assessing hunger levels in experiments is often biased, when using self-report methods, or complex, when using blood tests. We propose a novel way of objectively measuring subjects’ levels of hunger by identifying levels of alpha-amylase enzyme in their saliva samples. We used this measure to uncover the effect of hunger on different types of choice behaviors. We found that hunger increases risk-seeking behavior in a lottery-choice task, modifies levels of vindictiveness in a social decision-making task, but does not have a detectible effect on economic inconsistency in a budget-set choice task. Importantly, these findings were moderated by alpha-amylase levels and not by self-report measures. We demonstrate the effects hunger has on choice behavior and the problematic nature of subjective measures of physiological states, and propose to use reliable and valid biologically-based methods to overcome these problems.